The Influence of Employee Retention, Job Satisfaction, and Work Motivation on Employee Performance at PT. Asri Buana Image - Hanifa Nurul Hida Hakim; Sudarijati; Erni Yuningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of employee retention, job satisfaction, and work motivation on employee performance at PT. Citra Asri Buana both simultaneously and partially. The subjects of this research were employees of PT. Citra Asri Buana as many as 50 employees as samples. The form of this research is descriptive and verification. Data collection procedures in this research used literature studies, field studies, interviews, observations and questionnaires. The data analysis method used is multiple linear regression analysis. The results of the validity and reliability tests show that all statement items are declared valid and reliable. The results of this research show that employee retention, job satisfaction and work motivation meet good criteria. Simultaneously and partially employee retention, job satisfaction and work motivation have a positive and significant effect on employee performance.